Health Promoting Opportunities in Urban Environment - Vinck, Jan (ANIMA Indonesian Psychological Journal, 2007)
This paper is attempted to answer to the question ”How can psychologists, using psycho- logical science, contribute to the prevention of illness and to the promotion of health, particularly in an urban environment?” It will be shown that in this ecological approach the urban environment is of crucial importance, which opens health promoting opportunities. Media advertise for specific prod- ucts and have an influence on sale; they create social models, social norms and stereotypes. Social and cultural forces have an impact on stereotypes with regards to healthy and risky behaviour. The educational system has, in collaboration with parents, an important role in shaping healthy behaviour and establishing healthy social norms. We draw a conclusion that we should stop focusing (almost exclusively) on individual responsibility and rationality, understand health related behaviour as habits and move to working with the situational contingencies that are eliciting and reinforcing behaviour. Artikel ini berupaya menjawab pertanyaan “Bagaimana para psikolog, dengan ilmunya, mampu berkontribusi pada pencegahan penyakit dan promosi kesehatan, terutama dalam lingkungan perkotaan?” Akan ditunjukkan bahwa dalam pendekatan ekologis ini, lingkungan perkotaan amat me- nentukan, yang memberi kesempatan mempromosikan kesehatan. Media mengiklankan produk- produk spesifik dan memengaruhi penjualan; mereka menciptakan model sosial, norma dan stereotip sosial. Kekuatan sosial dan budaya memiliki dampak pada stereotip yang menyangkut perilaku sehat maupun berisiko. Sistem pendidikan memiliki, dalam kerja sama dengan para orang tua, peran penting dalam membentuk perilaku sehat dan mengukuhkan norma sosial yang sehat. Kami menarik simpulan bahwa kami harus mampu berhenti menuntut (nyaris secara eksklusif) tanggung jawab dan rasionalitas individual, memahami bahwa perilaku terkait kesehatan adalah suatu kebiasaan dan mulai bekerja dengan kemungkinan situasional yang mencetuskan dan menguatkan perilaku.